Use of Sewage Sludge in the Production of Plant Biomass for Energy: Biological and Economic Conditions; Biologiczne i ekonomiczne uwarunkowania zastosowania osadoẃ sćiekowych w produkcji biomasy rosĺinnej na cele energetyczne - Zdzisława Romanowska-Duda; Mieczysław Grzesik; Wiktor Pszczoĺkowski; Agata Pszczoĺkowska; Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
The goal of this article is a presentation of the legal, biological, and economic conditions of energy production using biomass, especially taking into account the application of sewage sludge certified for natural use in agriculture. Any increase in the production of biomass necessitates the introduction of cheap and highly-efficient plant production technologies that are environmentally- friendly. Use of certified sewage sludge can increase the economic efficiency of energy crops and have a beneficial impact on the environment. – – Celem artykułu jest przedstawienie prawnych, biologicznych i ekonomicznych uwarunkowanṕrodukcji energii z biomasy rosĺinnej, ze szczegoĺnym uwzglednieniem zastosowania osadoẃ sćiekowych majacych certyfikat przyrodniczego wykorzystania w rolnictwie. Zwiekszenie produkcji biomasy wymaga wprowadzenia tanich i wysokowydajnych technologii produkcji rosĺin przyjaznych sŕodowisku. Zastosowanie certyfikowanych osadoẃ sćiekowych zwieksza efektywnosćékonomiczna upraw energetycznych i korzystnie wpływa na sŕodowisko.
Keywords: 330